Effect of plant density and foliar fertilizer spray on growth and yield of netted melon (Cucumis melo L.) ‘Inthanon RZ’ - Hai, Truong Thi Hong; Thao, Phan Thu (Hue University Journal of Science: Natural Science, 2021)
The cultivation of netted melon is becoming popular in vegetable farms in Vietnam. The netted melon cultivar ‘Inthanon RZ’ was evaluated for its growth ability, yield, fruit quality, and economic efficiency when treated with densities of 38,000 and 33,000 plants/ha and four foliar fertilizer sprays: Biotic foliar AMINO ACID 1000, NPK NUTRI-GOLD 29-10-10 + 3 MgO + TE, NPK HAI-CHYODA 14-17-12 + 12 S, and NPK DAU TRAU 30-10-5 + TE. The experiment was conducted in a plastic house at the Biotechnology Institute of Hue University from January to April 2019. The experiment area was 72 m2. The results indicate that plants have a similar growth time under the cultivation conditions. The plants grown with the density of 38,000 plants/ha exhibit a higher leaf area index. The actual yield ranges from 34.00 tons/ha (AMINO ACID 1000; 33,000 plants/ha) to 46.22 tons/ha (NPK HAI-CHYODA 14-17-12 + 12 S; 38,000 plants/ha). Applying NPK HAI-CHYODA 14-17-12 + 12S or NPK DAU TRAU results in the Brix grade higher than 12.0 for both plant densities. Powdery mildew is the most frequently observed in the treatments with NPK DAU TRAU. The yield and profit obtained from trading the melon are highest for the density of 38,000 plants/ha with fertilizer NPK HAI-CHYODA 14-17-12 + 12S.